Urinary Excretion of 17- ketosteroids and 17-21 Dihydroxy -20- ketosteroids in Native Sea Level and Height - Pretell Zárate, Eduardo (1961)
We did not find differences between high altitude natives and native sea level in the urinary excretion of 17- ketosteroids and 17,21 - dihydroxy -20- ketosteroids in baseline conditions . After intravenous administration of hydrocortisone , the amount of urinary steroids appearing in the urine within 24 hours , is equal to the high altitude native and native sea level. This result is interpreted to mean that the catabolism of hydrocortisone is also similar , and that the same urinary excretion at baseline reflects equal hydrocortisone production by the adrenal cortex . By inhibiting the endogenous corticotrophin, by dexamethasone , urinary excretion of steroids in equal magnitude decreases in the two groups studied . This result is interpreted in the sense that equality in the production of hydrocortisone is intrinsically dependent on the adrenal cortex.